2014
DOI: 10.1111/pce.12308
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit induces chlorophyll degradation via the ‘PAO/phyllobilin’ pathway in leaves of homoio‐ (Craterostigma pumilum) and poikilochlorophyllous (Xerophyta viscosa) resurrection plants

Abstract: Angiosperm resurrection plants exhibit poikilo-or homoiochlorophylly as a response to water deficit. Both strategies are generally considered as effective mechanisms to reduce oxidative stress associated with photosynthetic activity under water deficiency. The mechanism of water deficit-induced chlorophyll (Chl) degradation in resurrection plants is unknown but has previously been suggested to occur as a result of non-enzymatic photooxidation. We investigated Chl degradation during dehydration in both poikiloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 91 publications
0
31
0
Order By: Relevance
“…Sap flow of vital poplar started to decrease from 19:00 p.m., which was 2 h later than the senesced poplar, which may have been decided by the physiological and morphological status of the tree itself. Hörtensteiner's study showed that chlorophyll content in tree leaves decreased when the tree leaves were senesced [50]; furthermore, Christ et al found that water shortage also induced decreasing chlorophyll in tree leaves [51], however, the lower chlorophyll content in tree leaves weakened the photosynthetic activity …”
Section: Discussionmentioning
confidence: 99%
“…Sap flow of vital poplar started to decrease from 19:00 p.m., which was 2 h later than the senesced poplar, which may have been decided by the physiological and morphological status of the tree itself. Hörtensteiner's study showed that chlorophyll content in tree leaves decreased when the tree leaves were senesced [50]; furthermore, Christ et al found that water shortage also induced decreasing chlorophyll in tree leaves [51], however, the lower chlorophyll content in tree leaves weakened the photosynthetic activity …”
Section: Discussionmentioning
confidence: 99%
“…In both X. humilis and X. viscosa, Chl degradation begins once leaf water content decreases below 80% RWC and continues to depletion in the air-dry state. During rehydration, Chl biosynthesis is induced rapidly, and the regeneration of thylakoids is apparent within 3 d (Ingle et al, 2008;Christ et al, 2014). This poikilochlorophyllous mechanism bears a strong resemblance to the degradation of Chl in maturing seeds.…”
Section: Regulated Shutdown Of Photosynthesis In Poikilochlorophylloumentioning
confidence: 95%
“…1), such as Xerophyta humilis and X. viscosa, gradually dismantle their photosynthetic machinery, leading to almost Chlfree dehydrated leaves ( Fig. 2; Porembski, 2011;Tuba and Lichtenthaler, 2011;Beckett et al, 2012;Christ et al, 2014). In both X. humilis and X. viscosa, Chl degradation begins once leaf water content decreases below 80% RWC and continues to depletion in the air-dry state.…”
Section: Regulated Shutdown Of Photosynthesis In Poikilochlorophylloumentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related with the lower specific leaf area of M. exsucca, respect to L. chequen which could involve a higher density of PS and a higher probability of photochemicals process in the same area (Vile et al 2005, He et al 2013. Drought reduction in pigment content has been considered a typical symptom of oxidative stress, as a result of either slow synthesis or fast breakdown (Christ et al 2014).…”
Section: Discussionmentioning
confidence: 99%